CHARACTERISTIC TESTING OF EDIBLE FILM FROM CASSAVA PEEL STARCH (Manihot esculenta) BASED ON THE EFFECT OF GLYCEROL VARIATION CHARACTERIZATION - Salmah Tiara Azmi; Devi Tanggasari (Universitas Muhammadiyah Mataram, 2025)
Edible film is a thin layer that functions as a coating for food products, made from natural and consumable materials. One of the materials used in this study is cassava peel starch, which is suspended with glycerol and agar as plasticizers. This study aims to determine the characteristics of Edible film made from cassava peel starch and agar with the addition of different glycerol concentrations. The research was conducted using an experimental method and designed with a Completely Randomized Design (CRD), with glycerol treatments of 1,5 ml (P1), 2 ml (P2), and 2,5 ml (P3). The results showed that variations in glycerol concentration affected the biodegradation rate but did not significantly influence thickness, solubility, and absorption capacity of the Edible film. The best absorption capacity was observed at 1,5 ml of glycerol, while the best results for thickness, solubility, and biodegradability were found at 2.5 ml of glycerol. The use of 2,5 ml of glycerol is recommended as the optimal treatment in terms of both physical and microbiological properties, with the following characteristics: thickness of 0,19 mm, solubility of 40,8%, film absorption capacity of 29,7%, and film biodegradability of 79,3%, with a degradation rate of 10,9 mg/day.